The Rise in Comovement Across National Stock Markets : Market Integration or Global Bubble? - Brooks, Robin (IMF Working Papers; Working Paper ;, 2002)
The degree of comovement across national stock markets has increased dramatically since the mid-1990s. This has overturned a stylized fact in the international portfolio diversification literature that diversifying across countries is more effective for risk reduction than diversifying across industries. We investigate if this rise in comovement is a permanent phenomenon driven by greater economic and financial integration, or a temporary effect associated with the recent stock market bubble. At the global level, our results point to the bubble. At a regional level, we find evidence of a significant rise in market integration within Europe, possibly a reflection of institutional changes such as the EMU.